Comparative analysis of Windows Presentation Foundation and Windows Forms - Pasztaleniec, Michał; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2020)
The article presents a comparison of two technologies for creating desktop applications based on C#. The analysis conserns the use of the processor, RAM and time of the operation was carried out on the technologies of Windows Presentation Foundation and Windows Forms. The research use applications with the same functionality in both technologies. The comparative analysis took into account the times of operations and application performance.